Cell Wall Layer Induced in Xylem Fibers of Flax Upon Gravistimulation Is Similar to Constitutively Formed Cell Walls of Bast Fibers - Petrova, Anna; Kozlova, Liudmila; Gorshkov, Oleg; Nazipova, Alsu; Ageeva, Marina; Gorshkova, Tatyana (Frontiers in Plant Science, 2021)
In the fibers of many plant species after the formation of secondary cell walls, cellulose-enriched cell wall layers (often named G-layers or tertiary cell walls) are deposited that are important in many physiological situations. Flax (Linum usitatissimum L.) phloem fibers constitutively develop tertiary cell walls during normal plant growth. During the gravitropic response after plant inclination, the deposition of a cellulose-enriched cell wall layer is induced in xylem fibers on one side of the stem, providing a system similar to that of tension wood in angiosperm trees. Atomic force microscopy, immunochemistry, and transcriptomic analyses demonstrated the G-layer induced in flax xylem fibers was similar to the constitutively formed tertiary cell wall of bast (phloem) fibers but different from the secondary cell wall. The tertiary cell walls, independent of tissue of origin and inducibility, were twice as stiff as the secondary cell walls. In the gravitropic response, the tertiary cell wall deposition rate in xylem was higher than that of the secondary cell wall. Rhamnogalacturonan I with galactan side chains was a prominent component in cellulose-rich layers of both phloem and xylem flax fibers. Transcriptomic events underlying G-layer deposition in phloem and xylem fibers had much in common. At the induction of tertiary cell wall deposition, several genes for rhamnosyltransferases of the GT106 family were activated in xylem samples. The same genes were expressed in the isolated phloem fibers depositing tertiary cell wall. The comparison of transcriptomes in fibers with both inducible and constitutive tertiary cell wall deposition and xylem tissues that formed secondary cell walls is an effective system that revealed important molecular players involved in the formation of cellulose-enriched cell walls.